Philosophy, politics and language in conversation with the academy: Volume I - Montero González, Martha Soledad; Páez Guzmán, Esaú Ricardo; Universidad Pedagógica y Tecnológica de Colombia; Raffin, Marcelo; López, Cristina; Trina, Miguel Ángel; Universidad de Chile; Osorio Tamayo, Daniel Ernesto; Barreto Chica, Omaira; Bula Caraballo, Germán Ulises; Universidad de La Salle; Rodríguez García, Hernán Ferney; Universidad de La Salle; García Salazar, Edwin; Ríos Padilla, Joséphine Aruma (UPTC Editorial, 2022)
The idea of gathering and presenting, in this book, the advances of the research carried out within the Philosophy, Education and Pedagogy research group has to do with the purpose, among other things, of having a record of work and the voices that year after year give an account of the development of the Research Project Training of new researchers. Thus, here the reader will be able to find investigations that, in some cases, present initial advances, in other cases, they indicate the developments or the closure of their production processes. Investigations that are defining problems, establishing limits and building paths to give  answers to the concerns that arise in the fields of education and training, history, philosophy, politics and language; concerns that, given the specificity of the social sciences, cross a set of disciplinesthat allow accounting for the different objects of study. It is in this territory that we move.